Jurnal Riset dan Inovasi Peternakan - Teguh Rafian (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2023)
Chief Editor Kusuma Adhianto Associate Editor Dian Septinova Ratna Ermawati Fitria Tsani Farda Etha ‘Azizah Hasiib Editorial Board Rudy Sutrisna Farida Fathul Ali Husni Erwanto Rr. Riyanti Syahrio Tantalo Khaira Nova Sri Suharyati Purnama Edy Santosa Siswanto Liman Teguh Rafian